Photosensitizing Properties of Alkynylrhenium(I) Complexes [Re(–C≡C–R)(CO)3(N∩N)] (N∩N = 2, 2′‐bipy, phen) for H2 Production. Issue 19 (July 2014) - Oberholzer, Miriam; Probst, Benjamin; Bernasconi, Dominik; Spingler, Bernhard; Alberto, Roger
Abstract: Invited for the cover of this issue is the group of Roger Alberto at the University of Zürich, Switzerland. The cover image shows the reduction of protons by illumination of a catalytic mixture containing a cobalt‐based water‐reduction catalyst (WRC), a rhenium(I)–alkynyl photosensitizer, a proton source (H + ), and a sacrificial electron donor (D/D + ). The final product, hydrogen gas, stores the energy of light in its chemical bond. Abstract : One of the main challenges of our research is to combine water oxidation and water reduction in one system to finally split water into hydrogen and oxygen... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 3002 ff .